The Role Of Independent Commissioners In Moderating The Effect Of Transfer Pricing, Capital Intensity And Profitability Towards Tax Aggressivity - Nuryatun Nuryatun; Susi Dwi Mulyani (Universitas Trisakti, 2020)
Tax is a sector that plays an important role in the economy. The largest state revenue must continue to be increased so that the country's growth and development can run well. But for business tax as a burden. Therefore, it is only natural to try to avoid the tax burden. Management actions planned to minimize corporate tax payments through tax aggressiveness activities are common among companies throughout the world. This study aims to see the role of independent commissioners in moderating the effect of transfer pricing, capital intensity and profitability on tax aggressiveness. The population and sample in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period. The sampling method used was purposive sampling. The analysis tool used is panel data regression analysis. The results showed that 1). Capital intensity and profitability each have a positive effect on tax aggressiveness. 2). Transfer prices and independent commissioners are not subject to tax aggressiveness. 3). Independent commissioners can moderate weaken the influence of capital on tax aggressiveness. 4). Independent Commissioners as measured by the Total Board of Commissioners divided by the Independent Commissioners (KI) are unable to assess or weaken the relationship between transfer pricing profitability and tax aggressiveness.